Group Delay Reduction Methods in FIR Digital Filters - Al-Ani, Hala Haseeb (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2013)
Linear-phase finite impulse response (FIR) filters are widely used in digital signal processing applications because of their various advantages. These advantages include the absence of phase distortion, unrestricted stability, and lower filter-coefficient sensitivity. The most important shortcoming of linear-phase FIR filter is that the overall group delay is (N-1)/2 where N is the length of the filter. This quantity becomes large for higher order filters in communication applications. Many algorithms have been proposed to reduce this delay and its distortion. Typically, block convolution techniques such as overlap-add method (OAM) and overlap-save method (OSM) are used for a long input sequence. Yet, with respect to input, by using these methods, the output sequence has a finite group delay. In this thesis, the performance of enhanced modified overlap and save method is investigated. First, the impulse response is made causal and then it is shifted left (circular) by an amount of for odd and for even. Finally, the samples to be excluded from the final convolution are defined. It is expected that this results in a reduction in the causal delay and also in the group delay. Simulations are carried out by MATLAB. The performance of the method is compared with the results obtained from the OSM based filter. Keywords: Impulse Response, FIR Filter, Linear Phase FIR Filter, Group Delay.

ÖZ: Doğrusal fazlı sonlu dürtü cevaplı (FIR) süzgeçler çok çeşitli avantajlarından dolayı, sayısal sinyal işleme uygulamalarında yaygın olarak kullanılmaktadırlar. Bu avantajlar, faz bozunumu içermeyen, sınırsız kararlılık ve süzgeç katsayılarına olan az duyarlılık olarak sıralanabilir. Ancak, doğrusal fazlı FIR süzgeçlerinin en önemli dezavantajı ise toplam grup gecikmesinin (N-1)/2 olarak ortaya çıkmasıdır. Buradaki N, süzgeçteki katsayı sayısını temsil etmektedir. Haberleşme uygulamalarında, toplam gecikmenin miktarı süzgeç katsayılarının sayıları ile doğru orantılı olarak artmaktadır. Bu gecikmeyi ve ondan dolayı oluşan bozunumu azaltmak için birçok algoritma önerilmiştir. Tipik olarak, uzun giriş dizileri için blok konvolüsyon olarak bilinen üstüste binik toplama metodu (OAM) ve üstüste binik saklama metodu (OSM) kullanılır. Bu metodlar kullanıldığında, çıkış dizisinin girişe göre sonlu bir grup gecikmesi vardır. Bu tezde, iyileştirilip modifiye edilmiş üstüste binik saklama metodunun performansı incelemiştir. İlk olarak, süzgeçin dürtü cevabı nedensel yapılmıştır ve bu dürtü cevabı daha sonra, N tek olduğu zaman (N-1)/2 kadar sola, çift olduğu zaman ise N/2 kadar yine sola kaydırılmıştır. Son olarak, son konvolüsyon sonucundan dışlanacak olan örnekler tanımlanmıştır. Bunun, nedensel gecikme ve grup gecikmesinin azalmasına neden olacağı beklenmektedir. Benzetim çalışmaları MATLAB ortamında yapılarak, bu metodun performansı, OSM metodundan elde edilen sonuçlarla karşılaştırılmıştır. Anahtar kelimeler: Dürtü Cevabı, FIR Süzgeç, Doğrusal Fazlı FIR Süzgeç, Grup Gecikmesi
Master of Science in Computer Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Computer Engineering, 2013. Supervisor: Prof. Dr. Hasan Kömürcügil
Keywords: Computer Engineering; Speech Processing Systems - Digital Signal Processing; Impulse Response; FIR Filter; Linear Phase FIR Filter; Group Delay